The Burka Ban: Islamic Dress, Freedom and Choice in The Netherlands in Light of the 2019 Burka Ban Law - Bat-sheva Hass (Religions, 2020)
This article, part of an evolving and large project, examines the relationship between clothing, freedom and choice, and specifically Islamic dress in shaping the identity of Dutch Muslim women after the Burka Ban that was voted into law on 1 August 2019 in the Netherlands. It discusses the debates before and after this date, as well as the background to the ban. A veil covering the face is a garment worn by some Muslim women to adhere to an interpretation of hijab (modest dress). It can be referred to as a burqa or niqab. In the aftermath of the Burka Ban that prompted considerable public alarm on the part of Muslim men and women, niqab-wearing women, as well as women who do not wear a veil, but are in solidarity with their niqabi sisters, raised a number of questions that form the basis for the analysis presented here: how do Dutch Muslim women shape their identity in a way that it is both Dutch and Muslim? Do they incorporate Dutch parameters into their Muslim identity, while at the same time weaving Islamic principles into their Dutch sense of self? The findings show how Islamic clothing can be mobilized by Dutch Muslim women to serve identity formation and personal (religious) choice in the Netherlands, where Islam is largely considered by the non-Muslim population to be a religion that is oppressive and discriminatory towards women. It is argued that in the context of being Dutch and Muslim, these women express their freedom of choice through clothing, thus pushing the limits of the archetypal Dutch identity and criticizing Dutch society while simultaneously stretching the meaning of Islam to craft their own identity.